2022
DOI: 10.1002/pld3.398
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion by the interaction of a novel synthetic small molecule with GA‐DELLA function

Abstract: Synthesized small molecules are useful as tools to investigate hormonal signaling involved in plant growth and development. They are also important as agrochemicals to promote beneficial properties of crops in the field. We describe here the synthesis and mode of action of a novel growth‐promoting chemical, A1. A1 stimulates enhanced growth in both shoot and root tissues of plants, acting by increasing both dry and fresh weight. This suggests that A1 not only promotes uptake of water but also increases product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The target gene of miR171b-3p, PGSC0003DMG400012683 , encoded DELLA protein. DELLA proteins are important repressors of GA signaling ( Chai et al, 2022 ; Sukiran et al, 2022 ). Plant hormones are involved in anthocyanin biosynthesis, such as auxin ( Ji et al, 2015 ; Liu, Shi & Xie, 2014 ), abscisic acid (ABA) ( Balint & Reynolds, 2013 ; Leão et al, 2014 ) and gibberellic acid (GA) ( Loreti et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The target gene of miR171b-3p, PGSC0003DMG400012683 , encoded DELLA protein. DELLA proteins are important repressors of GA signaling ( Chai et al, 2022 ; Sukiran et al, 2022 ). Plant hormones are involved in anthocyanin biosynthesis, such as auxin ( Ji et al, 2015 ; Liu, Shi & Xie, 2014 ), abscisic acid (ABA) ( Balint & Reynolds, 2013 ; Leão et al, 2014 ) and gibberellic acid (GA) ( Loreti et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar experiment with the GA biosynthetic mutant ga1-5, which has low levels of GA and consequently is a dwarf and displays a shorter hypocotyl than the wild type [41,42], clearly revealed that A1 treatment was not able to rescue the hypocotyl elongation phenotype, thus pointing out that A1 requires both GA and DELLA for its growth-promoting effect. Surprisingly, the addition of the A1 compound could not rescue the hypocotyl phenotype of the GA receptors' gid double mutants, suggesting that this small compound acts upstream of the GA receptors [38]. Therefore, although this work presents an interesting compound able to increase plant growth, there is still a need to investigate the MoA (mode of action) of the A1 small molecule to make it a remarkable agrochemical candidate.…”
Section: Small Molecules To Gain Insights Into Plant Morphogenesis An...mentioning
confidence: 97%
“…Unveiling the mechanism of action of EH-1 will lead to insights into the action of ethylene and the ethylene-mediated triple response, while it could become a promising compound to improve the fruit yield of crop species. [32], A1 [38], LS [56], EH-1 [65], Phe-Ade [48], PPBo, NPA, TIBA and Kyn [54].…”
Section: Small Molecules To Gain Insights Into Plant Morphogenesis An...mentioning
confidence: 99%
See 2 more Smart Citations